Social Responsibility Practices Focused on Sustainable Development Implemented in Colombia SMEs - Quintero Rivera, Juan José; Cervantes Rosas, María de los Ángeles (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To analyze the social responsibility practices implemented by Colombian companies and their contribution to the Sustainable Development Goals (SDG) of the 2030 Agenda.MATERIAL AND METHOD: The research is classified as descriptive, with a documentary approach. To gather information on the practices implemented by Colombian companies, an exhaustive review of the literature and a thorough exploration of the websites of these companies were carried out. The main objective of this process was to identify specific practices and evaluate their contribution to the Sustainable Development Goals (SDGs) of the 2030 Agenda.RESULTS: 16 SME companies in Colombia were analyzed, highlighting CSR practices aligned with the Sustainable Development Goals (SDGs), these include aspects such as environmental sustainability, labor well-being and social responsibility, each company implements specific SDGs, such as SDG 12 for responsible consumption and SDG 13 for climate action, Table 3 presents the companies and their applied SDGs.CONCLUSIONS: The effects of climate change in Colombia include losses of 0.49% of annual GDP, affecting various sectors. SMEs adopt CSR practices focused on SDGs, with an emphasis on responsible production and consumption and labor well-being, but there is still room for improvement in sustainability.
Keywords: Responsible consumption; Social responsibility; Climate change; Sustainability.